Особенности интродукции и онтогенеза Chionodoxa lucilia Boiss. в условиях Донбасса - Павлова, М.А. (Промышленная ботаника, 2002)
Biomorphological peculiarities of Chionodoxa lucilia from introductional populations of Donetsk botanic gardens, Nat. Acad. Sci. of Ukraine have been studied: phenology, vegetative and generative organs morphology, capacity of vegetative and seed reproduction. The species three periods and seven age statuses, large life-cycle have been depicted.